Effect Of The Application Of Information And Communication Technology On Improving Innovation - Budi Santoso, Arief; Moeins, Anoesyrwan; Sunaryo, Widodo (Riviera Publishing, 2022)
This research aims to analyze the influence of the Application of Information and Communication Technology on improving the Asn Innovation of the Central Transportation Ministry. The number of samples in this study was 249 respondents using the slovin technique from all units in the Ministry of Transportation. Data collection is carried out using questionnaires, observations and interviews with related parties. The data analysis technique used is a mix method with multiple linear regression analysis and indicator analysis. The results showed that the variables of Application of Information and Communication Technology positively affected employee innovation at a significance level of 0.05 with a regression coefficient of each of them. There is a positive and significant influence the application of information and communication technology to The Innovative with a regression coefficient (?) of 0.136 and the resulting regression equation is Y ? 115.409 ? 0.136X3 , which means that each one-level increase in the Application of Information and Communication Technology results in an innovative increase of 0.136 at the constant 115,409. Thus, the application of information and communication technology is predicted to increase employee innovation. Based on the results of the determination test calculation, it can be known that the effective contribution (SE) variable of the Application of Information and Communication Technology (X3) to Innovation (Y) is 2.11%.